The Oxford handbook of fiduciary law - Criddle, Evan J.; Miller, Paul B. (Law teacher); Sitkoff, Robert H. (New York, NY : Oxford University Press, 2019)
The Oxford Handbook of Fiduciary Law provides a comprehensive overview of critical topics in fiduciary law and theory through chapters authored by leading scholars. The Handbook opens with surveys of the many fields of law in which fiduciary duties arise. Drawing on these surveys, the Handbook offers a synthetic analysis of fiduciary law's key concepts and principles. Chapters in the volume explore the defining features of fiduciary relationships, clarify the distinctive fiduciary duties that arise in these relationships, and identify the remedies available for breach of fiduciary duties. The Handbook also provides numerous comparative perspectives on fiduciary law from eminent legal historians and from scholars with deep expertise in a diverse array of the world's legal systems.
Fiduciary Principles in Fact-Based Fiduciary Relationships / Daniel B. Kelly -- Fiduciary Principles in Investment Advice / Arthur B. Laby -- Fiduciary Principles in Family Law / Elizabeth S. Scott, Ben Chen -- Fiduciary Principles in Surrogate Decision-Making / Nina A. Kohn -- Fiduciary Principles in Employment Law / Aditi Bagchi -- The Fiduciary Duties of Lawyers / Richard W. Painter -- Fiduciary Principles in Health Care / Mark A. Hall -- Fiduciary Principles and Public Offices / Ethan J. Leib, Stephen R. Galoob -- Fiduciary Principles and the State / D. Theodore Rave -- Fiduciary Principles in International Law / Evan J. Criddle -- The Identification of Fiduciary Relationships / Paul B. Miller -- Fiduciary Principles in Agency Law / Deborah A. DeMott -- The Fiduciary Duty of Loyalty / Andrew S. Gold -- The Fiduciary Duty of Care / John C. P. Goldberg -- Other Fiduciary Duties: Implementing Loyalty and Care / Robert H. Sitkoff -- Mandatory and Default Rules in Fiduciary Law / Daniel Clarry -- Fiduciary Remedies / Samuel L. Bray -- Fiduciary Principles in English Common Law / Joshua Getzler -- Fiduciary Principles in the Canon Law / Richard H. Helmholz -- Fiduciary Principles in Roman Law / David Johnston -- Fiduciary Principles in Classical Jewish Law / Chaim Saiman -- Fiduciary Principles in Trust Law / Robert H. Sitkoff -- Fiduciary Principles in Classical Islamic Law Systems / Mohammad Fadel -- Fiduciary Principles in Contemporary Common Law Systems / Matthew Conaglen -- Fiduciary Principles in European Civil Law Systems / t
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Trusts and trustees